Analysis of Innovation Attributes in The Innovation Adoption of Agricultural Mechanization Technology in Farmers - Dyah Gandasari (Institut Pertanian Bogor, 2021)
In the last 4-6 years, the government has provided an agricultural mechanization assistance through the Ministry of Agriculture to Gapoktan, Poktan or the Agricultural Equipment and Machinery Service Business (UPJA). Assistance is provided in order to support increased production and productivity of superior commodities. It is suspected that the use of alsintan has not been optimally utilized. In order to optimize the utilization of this government innovation, the optimization is carried out by analyzing the adoption and the use of alsintan and implementing the optimization of machinery. This study is limited to character analysis of the innovation that affects the speed of adoption of alsintan innovation in farmers in Bogor, Sukabumi and Cianjur districts. The unit of research analysis was individual alsintan user farmers. The samples were determined purposively. There were 158 selected respondents. The descriptive statistical analysis used was Microsoft Excel 2016. The results showed there were some influences of innovation attributes on the adoption of two-wheeled hand tractor and water pump innovations. Farmers can make use of innovation because it reduces production costs, makes work easier, and increases production. Besides, it is easy to use and easy to test; and the results are easy to see. Further research is needed to analyze the environment, organizations and individuals as the driving factors for innovation adoption.